Formulation And Evaluation Of Cross Linked Chitosan microspheres Containing Mitomycin-C - G.VINOTH KUMAR,; K.ANAND BABU., (International Journal of Pharma and Bio Sciences, 2011)
The purpose of this research was to formulate and systematically evaluate in vitro performances of chitosan microspheres containing Mitomycin-C. Chitosan microspheres containing Mitomycin-C were prepared by simple emulsification phase separation technique using glutaraldehyde as a cross-linking agent. Results of preliminary trials indicate that volume of cross-linking agent, time for cross-linking, polymer-to-drug ratio, and speed of rotation affected characteristics of microspheres. Microspheres were discrete, spherical, and free flowing. The microspheres exhibited good in vitro wash-off test and also showed high percentage drug entrapment efficiency. The best batch exhibited a high drug entrapment efficiency of 75% and a swelling index is 1.42. The drug release was also sustained for more than 12 hours. The polymer-to-drug ratio had a more significant effect on the dependent variables. The effect of chitosan concentration, cross linking agents and conditions were evaluated with respect to entrapment efficiency, particle size, surface characteristics and in vitro release behaviours.